Nanocompósitos contendo óleo essencial de Syzygium aromaticum : obstenção, caracterização e atividade larvicida contra o Aedes aegypti - Santos, Adriana de Jesus (2014)
The essential oils, such Syzygium aromaticum essential oil has attracted great interest due to their known larvicidal activity against the Aedes aegypti. However, these oils present a limited use in aqueous media, the proliferation media of Ae. aegypti. In this sense, the achievement of systems that improve the oil dispersion in aqueous media is highly necessary. The aim of the present work was to produce and characterize nanocomposite containing OESA as release system for larvicidal control of Ae. aegypti. The (bentonite/PVP) nanocomposites were produced via clay/polymer intercalation method using a hidroalcoholic solution. Samples with clay to polymer ratio of 2:1, 1:1 and 1:2 p/p were produced and they were characterized by X-ray diffraction (XRD), thermogravimetric analysis (TG/DTA), moisture determination by Karl Fischer method, differential scanning calorimetry and Fourier Transform Infrared Spectroscopy (FTIR). The larvicidal activity was evaluated though the determination of the median lethal concentration (CL50) for Ae. aegypti larvae. From XRD results, an increase in the basal spacing (d001) of bentonite from 13.61 Å to 27.13 Å could be observed after the nanocomposite formation, which characterizes the clay/polymer intercalation. When the oil was incorporated to the nanocomposite no difference could be detected in the basal spacing values. The TG/DTA and DSC curves suggested higher thermal stability for oil incorporated nanocomposite. The moisture determination by the Karl-Fischer method was used to confirm the TG results. From FTIR spectra it was possible to detect the vanishing and shifting of some OESA bands at 3075 cm-1, 2944 cm-1 e 1751 cm-1, which suggest the OESA incorporation to nanocomposite. The OESA presented CL50 of 40.74 ppm, while its major component eugenol presented CL50 of 48.19 ppm. The nanocomposite produced with a ratio of 2:1 p/p presented a CL50 of 27.34 ppm, which is less than the pure oil, suggesting the viability of the system.